2018
DOI: 10.1186/s12879-018-3358-4
|View full text |Cite
|
Sign up to set email alerts
|

Association between semi-quantitative microbial load and respiratory symptoms among Thai military recruits: a prospective cohort study

Abstract: BackgroundMultiplex real-time polymerase chain reaction assays have improved diagnostic sensitivity for a wide range of pathogens. However, co-detection of multiple agents and bacterial colonization make it difficult to distinguish between asymptomatic infection or illness aetiology. We assessed whether semi-quantitative microbial load data can differentiate between symptomatic and asymptomatic states for common respiratory pathogens.MethodsWe obtained throat and nasal swab samples from military trainees at tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…It is worth remembering that multiplex rPCR also detects the genomes of asymptomatic microbes, persistently infectious viruses, and normal bacterial flora. Therefore, the test does not necessarily signify clinical etiology [ 11 14 ]. As an example, a report that analyzed microbes in 312 non-acute specimens from military trainees using the same FTD33 kit showed that viruses and bacteria were present in 13.8 and 93.3% of throat and nasal swabs, respectively, from asymptomatic examinees [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It is worth remembering that multiplex rPCR also detects the genomes of asymptomatic microbes, persistently infectious viruses, and normal bacterial flora. Therefore, the test does not necessarily signify clinical etiology [ 11 14 ]. As an example, a report that analyzed microbes in 312 non-acute specimens from military trainees using the same FTD33 kit showed that viruses and bacteria were present in 13.8 and 93.3% of throat and nasal swabs, respectively, from asymptomatic examinees [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the test does not necessarily signify clinical etiology [ 11 14 ]. As an example, a report that analyzed microbes in 312 non-acute specimens from military trainees using the same FTD33 kit showed that viruses and bacteria were present in 13.8 and 93.3% of throat and nasal swabs, respectively, from asymptomatic examinees [ 11 ]. It is difficult to verify the clinical significance of the detected microbes using only multiplex rPCR.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…8,19,36 Across HAdV studies other than Feikin et al, 6 Schjelderup Nilsen et al 37 2019 reported that Ct values <30 were associated with respiratory tract infection (RTI), adjusted for age, gender and presence of other viruses; however, three other studies reported no associations between Ct values and symptom severity, hospitalization or LOS. 8,18,28 Aside from Feikin et al, 6 no further associations were reported across studies with HMPV and PiV, with exception of Fuller et al, 18 in which hospitalized paediatric patients (<5 years old) with PiV reported lower Ct values than controls (P = 0.047), and conversely, HMPV infections had lower Ct values in outpatients versus inpatients (P = 0.030), similar to the outcome for influenza. 8,28,38 In one study of herpes simplex virus (HSV), higher viral load was associated with increased mortality, disease severity and ICU admission; however, there were no other HSV respiratory studies identified in this review.…”
Section: Other Respiratory Pathogensmentioning
confidence: 95%